Research on Arch Model and Numerical Simulation of Critical Water and Sand Inrush in Coal Mine near Unconsolidated Layers - Guibin Zhang; Wenquan Zhang; Hailong Wang; Siwen Cao; Yuliang Wu; Zaiyong Wang (Geofluids)
With the continuous increase of the upper limit of coal mining, in mining areas near unconsolidated layers, water and sand inrush disasters occur from time to time, seriously threatening the safety of mine production. In this paper, the process of water and sand inrush accidents induced by mining near unconsolidated layers is analyzed using mechanical analysis and numerical simulation methods, based on the principle of silo unloading and arching and combined with actual water and sand inrush characteristics; the critical water and sand inrush arching mechanism is explained. The paper also proposed and established three critical arching mechanics models (interlocking arch, bonded arch, and transition arch), deduced the mathematical expression of interlocking arch and transition arch, and obtained the critical instability conditions of the arch and its influencing factors. The research results have guiding significance for the occurrence of water and sand inrush disasters and the judgment of the degree of damage in mining near unconsolidated layers.